2001
DOI: 10.1097/00005537-200108000-00022
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Quality of Life in Head and Neck Cancer Patients. Part II: Longitudinal Data

Abstract: Detailed knowledge about the differences between groups and changes over time may aid us in the communication with patients and in the design of intervention studies focusing on improvement of the support and rehabilitation of patients with head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
227
4
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(264 citation statements)
references
References 15 publications
(32 reference statements)
29
227
4
4
Order By: Relevance
“…Regarding radiation therapy side effects, according to our data as well as others', 29 the H&N35 seems to be very sensitive, indicating excellent discriminant validity in this respect. Stoeckli et al 30 do have results that differ from these; however, it is presumable that their data could not reach statistical significance levels because of the sample size-only 16 of their study participants had been irradiated.…”
Section: Discussionsupporting
confidence: 83%
“…Regarding radiation therapy side effects, according to our data as well as others', 29 the H&N35 seems to be very sensitive, indicating excellent discriminant validity in this respect. Stoeckli et al 30 do have results that differ from these; however, it is presumable that their data could not reach statistical significance levels because of the sample size-only 16 of their study participants had been irradiated.…”
Section: Discussionsupporting
confidence: 83%
“…In some studies no gender difference was noticed (23) whereas in others a worse QOL was reported for women (24 -26). Similarly, in some studies no influence of age on QOL was found (27) while in others better QOL was found among younger patients (28). Although not apparent in our study, tumour site has been reported as having a definite influence on the QOL among head and neck cancer patients (29).…”
Section: Discussionsupporting
confidence: 46%
“…observed a general trend of significant deterioration on quality of life during treatment but a slow recovery during the 12 following months (Bjordal et al, 2001).…”
Section: Cancer Treatment and Side-effectsmentioning
confidence: 93%